2005
DOI: 10.1093/chromsci/43.2.73
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC Method for the Simultaneous Determination of Amlodipine and Benazepril in Their Formulations

Abstract: A new, simple, precise, rapid, and selective high-performance thin-layer chromatographic (HPTLC) method is developed for the simultaneous analysis of amlodipine and benazepril in pharmaceutical formulations. The method uses zolpidem as an internal standard (IS). The stationary phase used is silica gel 60 F254 prewashed with methanol. The mobile phase consists of an ethyl acetate-methanol-ammonia solution (8.5:2.0:1.0, v/v/v). Detection and quantitation are performed densitometrically at lambda = 254 nm. The Rf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…However, there is very few analytical methods reported for the simultaneous analysis of these drugs in a combined dosage formulation [3,4]. The reported methods are UV spectrophotometric [5][6][7][8][9], Spectrofluorimetric [10] HPLC [11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPTLC [25,26], capillary electrophoresis [27][28][29][30] and electrochemical [31][32][33][34] methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is very few analytical methods reported for the simultaneous analysis of these drugs in a combined dosage formulation [3,4]. The reported methods are UV spectrophotometric [5][6][7][8][9], Spectrofluorimetric [10] HPLC [11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPTLC [25,26], capillary electrophoresis [27][28][29][30] and electrochemical [31][32][33][34] methods.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method is more sensitive than the reported LC 20 and HPTLC 21 methods. The cost of the analysis using LC-MS and GC-MS is very high and also very delicate instruments are needed compared to UPLC with respect to routine quality control analysis.…”
Section: Benazepril 2-[(3s)-3-[[(2s)-1-ethoxy-1-oxo-4-phenylbutan-2-mentioning
confidence: 83%
“…12 Similarly, a literature survey for BH revealed that few techniques have been reported for the determination of BH alone by HPLC, 13 HPTLC, 14 CE, 15 GC-MS, 16 LC-MS, 17 spectrophotometric detection 18 and by voltammetrically 19 from pharmaceutical dosage form. Only two methods have been reported for the simultaneous determination of AB and BH; one describes the RP-HPLC procedure 20 and the other describes HPTLC procedure, 21 but both these methods are time-consuming. So far, to our present knowledge, no ultra performance liquid chromatography (UPLC) method has been reported for the simultaneous determination of AB and BH in 2009 © The Japan Society for Analytical Chemistry † To whom correspondence should be addressed.…”
Section: Benazepril 2-[(3s)-3-[[(2s)-1-ethoxy-1-oxo-4-phenylbutan-2-mentioning
confidence: 99%
“…The derivative spectroscopy has also been applied for the determination of amlodipine and its photodegradant compound [8]. Chromatographic methods have been used widely for the analysis of AML, including thin layer chromatography (TLC) methods [9][10][11][12] and HPLC methods [13,14]. Capillary electrophoresis methods were also used for the analysis of AML in its formulations and biological fluids [15,16].…”
Section: Introductionmentioning
confidence: 99%